The results of the ecological study of different ecotypes of spring barley varieties in the dry conditions of the Volgograd Province - G. V. Kozubovskaya; V. I. Balakshina (Труды по прикладной ботанике, генетике и селекции)
Background. The main limiting factor for achieving high barley yields is the insufficient moisture availability for crops in certain periods of development. When comparing growing conditions with the requirements of varieties of different ecotypes to the conditions of plant growth and development, it is necessary to identify varieties that are resistant to drought at different stages of organogenesis and thus can be used as sources of drought resistance in barley breeding.Materials and methods. The study was carried out in the dry-steppe zone of the Volgograd Province at the experiment station of the Lower-Volga Research Institute of Agriculture. A nursery was laid out according to a standard method. Twenty-two varieties from Russia, the USA, Canada, Belarus and Germany were selected for the study, and 'Donetskiy 8' was used as a reference.Results and conclusions. In the dry-steppe zone, the moistening conditions at the booting stage and the temperature regime during ripening are important for the growth and development of spring barley. With sufficient moisture supply (56.3 mm) at the booting stage and moderate air temperature (the sum of active temperatures of 711°C) during the maturing stage, the grain yield was maximal and reached 7.08.0 tons/ha for individual varieties. In the absence of precipitation (1.4 mm) at the booting stage and strong heat during the maturing stage (1030.5°C), the yield of these varieties decreased to 2.5- 3.0 tons/ha. The coefficient of variation in more droughty years was 30-54%, while in wet ones it was 20.5%. The varieties that are suitable for the zone of risky agriculture as the most flexible ones that ensure high yields regardless of climatic conditions, are 'Miar', 'Donetskiy 8', 'Tetonia', 'PWA 1758', 'Lenetah', 'Hays', which adaptation coefficient is above 1 throughout the years of the study. A sharp response to the changing vegetation conditions was displayed by 'Omskiy Golozernyi', 'Dublet', 'Fobos', 'Tercel' and 'Thual', all with an adaptation coefficient below 1. The naked varieties 'Tamalpais' (USA) and 'CDCGainer' (Canada) have a high adaptation coefficient (1.23, 1.41) in arid conditions and can be used in barley breeding for drought resistance.